Ontogênese do seguimento de instruções: o papel da formação de classes de equivalência - Postalli, Lidia Maria Marson (2007)
Responding under the control of verbal commands is an important component of human learning. The stimulus equivalence paradigm, as a model of symbolic behavior, is useful in explaining how instructions specify contingencies of reinforcement: Words can become members of equivalence classes with other stimuli (the referents) such as objects, actions, relations, etc. This study investigated the formation of stimulus classes among pseudo-words (verbs) and phrases (verbs and nouns). The specific goals were to verify 1) whether the pseudo-words would become equivalent to actions and objects (presented as recorded videotapes) and abstract pictures; 2) whether the words and pictures would acquire instructional control over the non-verbal responding (performing the actions, in isolation or directed to objects). Two experiments were conducted with children aged four to six years. Experiment I used verb-like pseudo-words (Set A), actions without a particular name established by the verbal community to which the participants belonged (Set B) and colorful abstract pictures (Set C). In Experiment II the auditory stimuli were pseudo-phrases (verb-object) and the videotaped actions were directed to objects. Matching-to-sample procedures, with three comparison stimuli, were used in both experiments to establish conditional discriminations among stimuli of Sets A and B (AB relations) and among stimuli of Sets A and C (AC relations) and test for class formation (BC and CB probe trials interspersed among baseline trials). In both experiments, all children learned the baseline of conditional discriminations AB and AC and demonstrated the formation of equivalence classes (BC and CB), relating, without direct training, pseudo-words or phrases, actions and abstract pictures. Tests for instructional control, conducted at the beginning of the study (pre-test), after children learned the conditional discriminations (intermediate test) and after the formation of classes (post-tests) demonstrated that the baseline was sufficient for establishing the control by spoken instructions, but not by the corresponding abstract pictures. After class formation, all children followed both kinds of instructions . However, when tests in Experiment II presented new phrases (recombinations of words from learned phrases), no children showed recombinative generalization. This raises a question about the necessary and sufficient conditions for establishing a generalized repertoire of instruction following based on equivalence relations. The present results replicated and extended the results of previous studies on equivalence relations as a mechanism by which instruction following could emerge as a derived repertoire, without explicit training